2009
DOI: 10.1017/s000711450999047x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo metabolic tracking of 14C-radiolabelled isoflavones in kudzu (Pueraria lobata) and red clover (Trifolium pratense) extracts

Abstract: Absorption, distribution and elimination of 14C-labelled isoflavone-containing extracts from kudzu (Pueraria lobata) root culture and red clover (Trifolium pratense) cell culture were investigated in an in vivo rat model. The predominant isoflavones in the kudzu extract were the glycosides puerarin, daidzin and malonyl daidzin, while in the red clover extract, the major isoflavones were formononetin and its derivatives, genistein and biochanin A, with radioactivities of 3.770 and 7.256 MBq/g, respectively. Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…Isoflavone aglycones, for instance, are absorbed faster and in higher amounts than their glucosides. 40 A plateau in serum concentration at four hours after gavage, which followed the trend seen in the metabolic tracking of 14 C-kudzu crude extract, 27 is consistent with the enterohepatic circulation of kudzu isoflavones. 41 Plasma collected 24 h after gavage showed no difference in 14 C activity compared with serum collected 24 h after gavage.…”
Section: Metabolic Tracking Of Radiolabeled Isoflavone-rich Fractionsupporting
confidence: 62%
See 2 more Smart Citations
“…Isoflavone aglycones, for instance, are absorbed faster and in higher amounts than their glucosides. 40 A plateau in serum concentration at four hours after gavage, which followed the trend seen in the metabolic tracking of 14 C-kudzu crude extract, 27 is consistent with the enterohepatic circulation of kudzu isoflavones. 41 Plasma collected 24 h after gavage showed no difference in 14 C activity compared with serum collected 24 h after gavage.…”
Section: Metabolic Tracking Of Radiolabeled Isoflavone-rich Fractionsupporting
confidence: 62%
“…27 This may be attributed to the removal of non-target phytochemicals from the crude extract, including sugars, which would also have acquired radiolabel, and would have been readily absorbed and distributed throughout all animal tissues. Rats gavaged with the isoflavone-rich kudzu fraction accumulated 0.011%, 0.09% and 0.003% of the administered dose in each femur, tibia and vertebrae, respectively (Table 4).…”
Section: Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…Some minor malonyl glycosides, such as malonyl daidzin and malonyl genistin, were also reported from Gegen in the past decades [19][20][21]. To our knowledge, there were no C-glycoside malonyl conjugates reported till now.…”
Section: Research Articlementioning
confidence: 74%
“…Puerarin was able to protect neurons against the toxicity of 1-methyl-4-phenylpyridinium (MPP þ )-induced apoptosis and protect myocardium against ischemia and reperfusion injury [9,10]. By using 14 C radiolabeled analysis, puerarin had been shown to accumulate in bone tissues of rats, the femur, tibia, and vertebrae at 0.04%, 0.03%, and 0.01% of the oral administered dose, respectively [11]. A previous study also reported that puerarin promoted bone formation through activation of phosphatidylinositol-3-kinase/AKT pathway [3].…”
Section: Discussionmentioning
confidence: 99%